Convergence analysis of modified Picard-S hybrid iterative algorithms for total asymptotically nonexpansive mappings in Hadamard spaces. Issue 1 (1st February 2020) - Kumam, Wiyada; Pakkaranang, Nuttapol; Kumam, Poom; Cholamjiak, Prasit
ABSTRACT: In this paper, we introduce new type iterative scheme called a 'modified Picard- S hybrid' iterative algorithm to establish Δ-convergence and strong convergence theorems under suitable conditions for total asymptotically nonexpansive mappings in CAT(0) spaces. Our results in the paper improve and extend many results appeared in the literature. Moreover, we also illustrate numerical examples for the proposed iteration process to compare speed of convergence among the existing iterative algorithms.